Contraception for HIV-Infected Adolescents - Kourtis, Athena P. (Pediatrics, 2016)
Access to high-quality reproductive health care is important for adolescents and young adults with HIV infection to prevent unintended pregnancies, sexually transmitted infections, and secondary transmission of HIV to partners and children. As perinatally HIV-infected children mature into adolescence and adulthood and new HIV infections among adolescentsand young adults continue to occur in the United States, medical providers taking care of such individuals often face issues related to sexual and reproductive health. Challenges including drug interactions between several hormonal methods and antiretroviral agents make decisions regarding contraceptive options more complex for these adolescents. Dual protection, defined as the use of an effective contraceptive along with condoms, should be central to ongoing discussions with HIV-infected young women and couples wishing to avoid pregnancy. Last, reproductive health discussions need to be integrated with discussions on HIV care, because a reduction in plasma HIV viral load below the level of detection (an “undetectable viral load”) is essential for the individual’s health as well as for a reduction in HIV transmission to partners and children.